Theoretical and Practical Aspects of Strategic Management of Balanced Interaction between Subjects of Foreign Economic Activity and State Institutions - Rudnichenko, Yevhenii; Savina, Halyna; Franchuk, Vasil; Nestoryshen, Igor; Savin, Stanislav; Havlovska, Nataliia (TEM Journal, 2021)
The main purpose of this article is studying features of strategic management of the interaction of state institutions and enterprises from the position of finding compromise solutions, and the appropriate tools that allow ensuring a balance of interests of society and business in the implementation of foreign economic activity. The methodological basis of the study is game theory, since it is the most acceptable tool used if there is a conflict of interests of the parties. Moreover, the parties to such a conflict often make strategic decisions without knowing about the decisions of their opponents, which we observe in modern business. The game model of interaction between FEA participants and state institutions, developed in the main part of the study, is presented in the form of a non-coalition game. It has been established that the practical implementation of the found combined situation (solution of the game) fully relies on state institutions.